2018
DOI: 10.21873/invivo.11362
|View full text |Cite
|
Sign up to set email alerts
|

R0 Resection for Locally Advanced Pancreatic Cancer with Low-dose Gemcitabine with Wide Irradiation Area as Neoadjuvant Chemoradiotherapy

Abstract: NACRT with low-dose gemcitabine and wide irradiation area achieved 100% R0 resection and acceptable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Serum CA 19-9 levels are reportedly useful for perioperative management of patients with PDAC (16, 22), and the results of the present study suggest that patients with elevated Post-CA 19-9 levels are eligible for more intensive adjuvant or organ-specific treatment. Serum CA19-9 level is easy to monitor and has objective value, and prediction of elevated Post-CA19-9 levels can be helpful in selecting previously advocated preoperative treatments (23,24). In this patient series, high Pre-CA 19-9 levels supported preoperative treatment because of the increased risk of hepatic metastasis.…”
Section: Discussionmentioning
confidence: 75%
“…Serum CA 19-9 levels are reportedly useful for perioperative management of patients with PDAC (16, 22), and the results of the present study suggest that patients with elevated Post-CA 19-9 levels are eligible for more intensive adjuvant or organ-specific treatment. Serum CA19-9 level is easy to monitor and has objective value, and prediction of elevated Post-CA19-9 levels can be helpful in selecting previously advocated preoperative treatments (23,24). In this patient series, high Pre-CA 19-9 levels supported preoperative treatment because of the increased risk of hepatic metastasis.…”
Section: Discussionmentioning
confidence: 75%
“…In regards to low-dose gemcitabine, neoadjuvant chemoradiotherapy with a low dose of gemcitabine of 50–150 mg/m 2 per week has proved its effectiveness for locally advanced pancreatic cancer [ 42 , 43 , 44 , 45 ]. Various low doses of gemcitabine were administered for gemcitabine-based radiotherapy, and despite this low dose, excellent results were achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al demonstrated that initially unknown micro-metastases might be eliminated by preoperative therapy (18). Moreover, a recent study showed that CRT with full-dose gemcitabine may have local and systemic effects in improving the R0 resection rate and reducing micrometastases (19). In this meta-analysis, only 24 out of 72 total patients (30.5%) in the neoadjuvant CRT group had positive LN compared to 72 out of 92 (78.3%) total patients with positive LN rate in the upfront surgery group.…”
Section: Discussionmentioning
confidence: 99%